Selectivity of odorant receptors in insects - Bohbot, Jonathan D.; Dickens, Joseph C. (Frontiers in Cellular Neuroscience, 2012)
Insect olfactory receptors (ORs) detect chemicals, shape neuronal physiology and regulate behavior.  Although ORs have been categorized as “generalists” and “specialists” based on their ligand spectrum, both electrophysiological studies and recent pharmacological investigations show that ORs specifically recognize non-pheromonal compounds, and that our understanding of odorant-selectivity mirrors our knowledge of insect chemical ecology. As we are progressively becoming aware that ORs are activated through a variety of mechanisms, the molecular basis of odorant-selectivity and the corollary notion of broad-tuning need to be re-examined from a pharmacological and evolutionary perspective.